Activation of graphene aerogel with phosphoric acid for enhanced electrocapacitive performance. (October 2015) - Sun, Xiuxia; Cheng, Ping; Wang, Huanjing; Xu, Hua; Dang, Liqin; Liu, Zonghuai; Lei, Zhibin
Abstract: We present a facile and efficient route to introduce in-plane nanopores on the graphene sheets by activation of graphene aerogel (GA) with phosphoric acid (H3 PO4 ). Results from N2 adsorption and TEM images showed that H3 PO4 activation created mesopores with pore size of 2–8 nm on the graphene sheets. With such nanopores on graphene sheets, the activated GA exhibits a specific capacitance of 204 F g −1, enhanced rate capability (69% capacitance retention from 0.2 to 30 A g −1 ), reduced equivalent series resistance (3.8 mΩ) and shortened time constant (0.73 s) when comparing with the hydrothermally-derived pristine GA and thermally annealed GA in the absent of H3 PO4 . The excellent capacitive properties demonstrate that introduction of nanopores on GA by H3 PO4 activation not only provides large ion-accessible surface area for efficient charge storage, but also promotes the kinetics of electrolyte across the graphene two-dimensional planes.